To pimp a butterfly [compact disc] - Lamar, Kendrick, 1987- (Aftermath Entertainment, 2015)
Three years after the release of Good Kid, M.A.A.D. City, Kendrick Lamar releases his highly anticipated third album. Among the tracks is the new single The Blacker the Berry.